2017
DOI: 10.1111/hsc.12423
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patients' knowledge and views of about oral health and acceptability of related intervention in an Australian inpatient alcohol and drug treatment facility

Abstract: Social factors, health behaviours and the direct effects of substances contribute to the poor oral health and restricted access to dental services experienced by people who are dependent on drugs and/or alcohol. Admission for inpatient withdrawal management provides an opportunity for intervention to promote oral health but to be effective it must be acceptable to patients. To support intervention design, we examined patients' views about oral health, practices and treatment access, and appropriateness of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the first focus area, 23 studies were identified that included 3611 participants with a mean age ranging from 27.9 to 44 years [ 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The studies were conducted in Australia ( n = 2), Brazil ( n = 3), India ( n = 2), Indonesia ( n = 1), Iran ( n = 1), Ireland ( n = 2), Italy ( n = 2), Lithuania ( n = 1), Norway ( n = 1), Portugal ( n = 1), Serbia ( n = 1), South Africa ( n = 1), United Kingdom ( n = 1) and the United States ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…In the first focus area, 23 studies were identified that included 3611 participants with a mean age ranging from 27.9 to 44 years [ 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The studies were conducted in Australia ( n = 2), Brazil ( n = 3), India ( n = 2), Indonesia ( n = 1), Iran ( n = 1), Ireland ( n = 2), Italy ( n = 2), Lithuania ( n = 1), Norway ( n = 1), Portugal ( n = 1), Serbia ( n = 1), South Africa ( n = 1), United Kingdom ( n = 1) and the United States ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…A more universal approach to recommendations related to oral health, tobacco use, physical inactivity and dietary habits during AOD treatment should be considered. The irregularity in which these health behaviours were mentioned in guidelines was an unexpected finding of the review, particularly given literature reporting on the way that AOD services are well‐placed to deliver healthy lifestyle interventions [9, 11, 92–95].…”
Section: Discussionmentioning
confidence: 99%
“…Capacity building for implementation teams on the components of the program and the implementation processes has been reported to be a cornerstone of acceptability. 43,44 The fact that participants who felt capable of implementing the program and its associated processes were more likely to accept the program highlights the importance of imparting necessary skills to the implementers. Constructs related to 'feeling capable', such as perceived behaviour control 45 and self-control, 46 have been linked to actual performance of the respective behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that knowledge about the program was associated with acceptability is not surprising, but further underscores the importance of equipping implementers with relevant knowledge about the program. Capacity building for implementation teams on the components of the program and the implementation processes has been reported to be a cornerstone of acceptability 43,44 …”
Section: Discussionmentioning
confidence: 99%